Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.26717/bjstr.2018.11.002165
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacteriosis: A Global Threat

Abstract: Campylobacter species account for most cases of human gastrointestinal infections worldwide. In humans, Campylobacter bacteria cause illness called campylobacteriosis. It is a common problem in the developing and industrialized world in human population. Campylobacter species extensive research in many developed countries yielded over 7500 peer reviewed articles. In humans, most frequently isolated species had been Campylobacter jejuni, followed by Campylobactercoli (5-18.6 % of all Campylobacter cases), Campy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Campylobacter species are the leading cause of bacterial-derived food-borne diarrheal disease in humans worldwide [ 88 ], resulting mainly from the contamination of food of animal origin [ 89 , 90 ]. Campylobacter can colonize in most of the warm-blooded animals and poultry [ 91 ].…”
Section: Food-borne Zoonotic Bacterial Pathogensmentioning
confidence: 99%
See 2 more Smart Citations
“…Campylobacter species are the leading cause of bacterial-derived food-borne diarrheal disease in humans worldwide [ 88 ], resulting mainly from the contamination of food of animal origin [ 89 , 90 ]. Campylobacter can colonize in most of the warm-blooded animals and poultry [ 91 ].…”
Section: Food-borne Zoonotic Bacterial Pathogensmentioning
confidence: 99%
“…Campylobacter is a member of the family Campylobacteriaceae, which also includes the genera Arcobacter and the species Bacteroides ureolyticus [ 4 ]. The genus Campylobacter contains small (0.2–0.8 μ m × 0.5–5 μ m) [ 86 ], Gram-negative, curved, or spiral and microaerophilic bacteria [ 3 , 91 , 93 , 95 ] with a distinctive “darting” motility, and they are catalase- and oxidase-positive [ 89 , 90 ]. When two or more bacterial cells are grouped together, they form an “S” or a “V” shape of the gull wing [ 86 ].…”
Section: Food-borne Zoonotic Bacterial Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiologically, Campylobacter has been estimated to be responsible for diarrhea affecting 400-500 million people with 37,600 deaths worldwide annually (Mughal, 2018 ; WHO, 2018 ). However, much of its epidemiological aspects in middle east countries are still unknown (Kaakoush et al ., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, C. jejuni infection can also lead to auto-immune conditions of Guillain-Barré syndrome (GBS) and Miller Fisher syndrome [12]. Studies among under-five-year-old children showed that Campylobacter infection was as high as 17% [16]. This shows a threat to one of the most vulnerable groups.…”
Section: Introductionmentioning
confidence: 99%